Sequencing and identification of a cDNA clone for tomato polygalacturonase. - Grierson, D (1986)
The 2a isoenzyme of tomato polygalacturonase was purified from ripe fruit and characterised. The N-terminal amino acid sequence of the protein was determined in order to identify polygalacturonase cDNA clones. The nucleotide sequence of a ripening-related cDNA (pTOM 6) was determined and found to encode the N-terminal sequence of mature polygalacturonase 2a. The complete open reading frame encodes a polypeptide of molecular weight 50,051, including a putative pre-sequence of 71 amino acids.